Improving of Nursing Student Learning Achievements in Islamic Religion Subject Using Cooperative Methods Team Assisted Individualy (Tai) Model at School of Health Bina Sehat PPNI Mojokerto - ARIF EFENDI; ASEF WILDAN MUNFADLILA; MOH ZAINUDIN (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2018)
Islamic Education is an effort in the form of guidance and care for students so that after completing their education they can understand and practice the teachings of Islam and make it a way of life. The real purpose of this study is to find out the effect of using cooperative methods Assisted Individually Team (TAI) towards improving the learning achievement of Islamic religious studies for undergraduate students in Nursing School of health Bina Sehat PPNI Mojokerto. To realize this goal, more in-depth research is needed, namely by using quantitative methods with the type of quasi-experiment with the form of one group pre-test and post-test design. The population of the study was the 2nd semester students of class 1E 2017-2018 academic year at S1 Nursing School of health Bina Sehat PPNI Mojokerto. Sampling with class 1E purposive sampling technique for the second semester with 43 students. The results of the t-test were found to be 0, 00 <p value means that Ho was rejected and Hi was accepted, meaning that there was a significant influence on the use of cooperative methods assited individualy team type on learning achievement in Islamic religious courses.